From poverty to prosperity through diversity orchard - Singh, Sanjay Kumar; Nath, Vishal; Pongener, Alemwati; Pandey, S D (Indian Horticulture, 2022)
Orchardists always try to increase their yield and income from fruit crops they raise. Whatever crop they might cultivate, the bottom line is to invariably get a good price from their produce. Farmers can increase their income either by intensifying the existing enterprises or can move towards diversification (by growing new crops, new varieties), value-addition, or successful market linkages to improve their economic level. An excellent example of the strategy is Shri. Anoj Kumar Rai, a physics graduate, vibrant, successful and dynamic orchardist from remote village of Samastipur district of Bihar who was previously cultivating few crops. Now he has diversified his entire orchard with 32 fruit tree species with 115 commercial varieties besides his orchard adored with 33 varieties of mango expanded with at least 5 timber species. Besides providing regular knowledge to its neighbours, his activity is also creating avenues of alternative livelihood for village residents through fruit and varietal diversity, low chill temperate fruits also playing a significant role towards augmenting bountiful income not only for Malikaur village but also for the surrounding areas with curiosity. From the raising almost all fruit crops of the region, he has enhanced income by adopting value addition including harvesting, grading, packaging, processing, nursery husbandry practices himself and do self marketing to enhance his income with economic stability. This overall, is creating a virtuous cycle, which in turn is emboldening the society to attempt newer and more creative products and orchard designs.